2018
DOI: 10.1002/adbi.201800076
|View full text |Cite
|
Sign up to set email alerts
|

Perfused Organ Cell‐Dense Macrotissues Assembled from Prefabricated Living Microtissues

Abstract: Engineered tissues usually fall short of physiological cell densities and sizes, resulting in limited functional performance. Viability of large tissues is constrained by inadequate diffusion‐driven nutrient exchange. Methods to form large viable tissues are lacking and are constrained by diffusion‐driven nutrient exchange. Here, the use of the Bio‐Pick, Place, and Perfuse (Bio‐P3) is reported, an integrated biofabrication‐bioreactor platform that semiautomatically and rapidly assembles physiologically cell‐de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…To explore the confined self‐organization of cells, we employed cell‐repellent agarose hydrogel templates to realize topography‐induced aggregation ( Scheme ). Using HepG2 cells (a human hepatoma carcinoma cell line) as a model system, stable cellular aggregates with defined shapes were obtained after adding the cells (5 × 10 6 cells mL −1 ) into hydrogel templates for a 24 h culture (Scheme a). Taking advantage of defined hydrogel templates with different shapes (Figure S2, Supporting Information), cellular aggregates with simple shapes were first obtained such as toroid, trigonal ring, quadrangular ring, and pentagonal ring, where the templates provided a confined space for the aggregation and further fusion of cells ( Figure a–d).…”
Section: Resultsmentioning
confidence: 99%
“…To explore the confined self‐organization of cells, we employed cell‐repellent agarose hydrogel templates to realize topography‐induced aggregation ( Scheme ). Using HepG2 cells (a human hepatoma carcinoma cell line) as a model system, stable cellular aggregates with defined shapes were obtained after adding the cells (5 × 10 6 cells mL −1 ) into hydrogel templates for a 24 h culture (Scheme a). Taking advantage of defined hydrogel templates with different shapes (Figure S2, Supporting Information), cellular aggregates with simple shapes were first obtained such as toroid, trigonal ring, quadrangular ring, and pentagonal ring, where the templates provided a confined space for the aggregation and further fusion of cells ( Figure a–d).…”
Section: Resultsmentioning
confidence: 99%
“…Our approach represents a rapid and simple alternative for the bottom-up generation of scaffoldfree and well-organized artificial vascular beds at millimetric scale. In previous studies, millimetresized tissues have been commonly generated by using non-adhesive moulds [16,18,36] or coated plates [14,15], where spheroids are seeded on and allowed to aggregate. Although simple and inexpensive, these approaches often lead to formation of tissues with irregular sizes and geometries, displaying a low degree of organization due to random spheroid fusion [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…For biomanufacturing more complex structures, single spheroids can be subsequently fused into larger constructs [13], but current methodologies still present several limitations. A few studies have reported the formation of spheroid-based constructs, with dimensions in the range of 0.1-2 cm, by promoting spheroids fusion using non-adhesive wells and channels [14][15][16][17][18] or directional magnetic fields [19,20]. However, such methods often create constructs of irregular sizes, where spheroids are randomly packed [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of applications, the conjugation of 3D-printed liver tissues and microfluidic systems integrated with biosensors could enable real-time monitoring, thus introducing a new paradigm to the drug screening platform. Furthermore, micromanipulation technology could serve as one of the strategies to build volumetric liver tissue constructs ( Ip et al, 2018 ; Ayan et al, 2020 ). This technology enables the control of functional liver tissue blocks to assemble the blocks according to the predefined design; this is expected to efficiently produce volumetric liver tissues.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%